Productivity of Cattle Herd in Transhumance in Classified Forest of Upper Alibori Northern Benin - ASSANI SEIDOU, Alassan; ALKOIRET TRAORE, Ibrahim; HOUINATO, MARCEL ROMUALD BENJAMIN (My University, 2016)
A study involving 40 cattle herds with a total of 3645 head was carried out in the Classified Forest of Upper Alibori (northern Benin) to compare the productivity of four types of cattle breeding systems: the riparian small transhumant livestock (type 1), the riparian medium transhumant livestock (type 2), the national great transhumant livestock (type 3) and the cross-border transhumant (type 4). The type of cattle herd had a significant effect (p <0.05) on birth weight (17.8 vs. 16.6 vs. 21.0 vs. 23.4 kg), weight at three months (45.8 vs. 40.5 vs. 67.2 vs. 72.5 kg) five months of age (60.4 vs. 54.4 vs. 71.9 vs. 81.5 kg) for calves types 1, 2, 3 and 4 respectively. The type cattle herd had also a significant effect on the quantity of milk taken at the 4th week of lactation (4.7 vs. 1.5 vs. 1.1 kg) for types 1, 2 and 3 respectively. Demographic parameters (mortality rate, fertility rate and the proportion of cows) from herds surveyed were significantly (p <0.05) influenced by the type of cattle herd. Thus, the proportion of cows was higher (p <0.05) in herds of type 4 (33.8 vs. 33.4 vs. 20.4 and 29.6 % for types 3, 2 and 1 respectively). The annual mortinatality rate had higher (p<0.05) in the herds of types 3 and 4 (0.073 et 0.049/year vs. 0.022 et 0. 023 for types 1 and 2). The annual fecundity rate had higher (P<0.05) in type 1 herds (0.712 vs. 0.707 vs. 0.619 et 0,582/year for types 2, 3 and 4 respectively). The annual growth rate had higher (p <0.05) in herds of type 3 (0.237 vs. 0.225 vs. 0.160 et 0.142/year for types 1, 2 and 4 respectively). This study showed that animals of type 1 herds had the best demographic parameters, while herds of type 2 are distinguished by better milk. The types 3 and 4 herds had better growth performance production.
Keywords: Benin; herd’ structure; demographics parameters; growth; milk; protected area; transhumance.